Infrastructure and sectoral FDI in China: an empirical analysis - Faisal Mehmood; Muhammad Atique; Wang Bing; Hameed Khan; Henna Henna (Insights into Regional Development)
In this paper, for the first time, we investigate the relationship between infrastructure and sectoral distribution of FDI inflow in China. We use the Estimating Autoregressive Distributed Lag (ARDL) bound testing and Vector Error Correction Model (VECM) procedures of estimation. To unmask the shortcomings in the previous literature, we use a composite index of infrastructure with more than 30 indicators. The results show that there is a long-run relationship between sectoral FDI and infrastructure. A bidirectional causal relationship is confirmed by using VECM. However, we find unidirectional causality between the primary sector's FDI and infrastructure, and it is running from infrastructure to primary sector FDI. The inclusion of control variables, e.g., institutional quality, trade openness, and domestic investment, is robust in our analysis. The positive role of infrastructure in the sectoral distribution of FDI inflows is of utmost importance for policymakers and Chinese-government. Several policy implications are given in our study.